How can I thank you? Highlighting the benefactor's responsiveness or costs when expressing gratitude. (February 2021) - Park, Yoobin; Visserman, Mariko L.; Sisson, Natalie M.; Le, Bonnie M.; Stellar, Jennifer E.; Impett, Emily A.
Despite growing evidence that showing gratitude plays a powerful role in building social connections, little is known about how to best express gratitude to maximize its relational benefits. In this research, we examined how two key ways of expressing gratitude—conveying that the benefactor's kind action met one's needs (responsiveness-highlighting) and acknowledging how costly the action was (cost-highlighting)—impact benefactors' reactions to the gratitude and feelings about their relationship. Using observer ratings of gratitude expressions during couples' live interactions ( N = 111 couples), and benefactors' self-reports across a 14-day experience sampling study ( N = 463 daily reports), we found that responsiveness-highlighting was associated with benefactors' positive feelings about the gratitude expression and the relationship. In contrast, cost-highlighting had no such effect. These findings suggest that expressing gratitude in a way that highlights how responsive benefactors were may be critical to reaping the relational benefits of gratitude and have practical implications for improving couples' well-being.